A 3D-PRINTED, GRAPHENE-REINFORCED HYDROGEL SCAFFOLD FOR ENHANCED OSTEOGENIC DIFFERENTIATION OF MESENCHYMAL STEM CELLS - Anurogo, Dito (Journal of Biomedical and Techno Nanomaterials, 2025)
Bone tissue engineering requires scaffolds that replicate the mechanical stiffness and electroactive properties of native bone, features that conventional hydrogels lack. This study aimed to design, fabricate, and validate a 3D-printed graphene-reinforced hydrogel scaffold that enhances osteogenic differentiation of human mesenchymal stem cells (hMSCs) via combined mechanical and electrical stimulation. A composite bio-ink was developed by incorporating graphene nanoparticles (0, 0.1, 0.2, and 0.5% w/v) into a biocompatible hydrogel matrix, optimized for extrusion-based 3D printing. Scaffolds with a controlled pore size of 300 ?m were fabricated and analyzed for compressive strength, degradation kinetics, and electrical conductivity using a four-point probe. hMSCs were seeded onto the scaffolds and cultured under osteogenic conditions for 28 days. Osteogenic differentiation was assessed by alkaline phosphatase (ALP) activity (day 14), qPCR for RUNX2 and osteocalcin (OCN) (day 21), and Alizarin Red S staining for mineralization (day 28). Data were analyzed using ANOVA and regression modeling. The 0.2% w/v graphene-reinforced scaffolds showed optimal performance, with compressive strength of 35.0 MPa and electrical conductivity of 0.15 S/m, significantly higher than pure hydrogel controls. hMSCs cultured on these scaffolds exhibited increased ALP activity, upregulation of RUNX2 and OCN, and enhanced mineralization. At 0.5% w/v graphene, excessive viscosity hindered printability and reduced cell viability. Overall, the 3D-printed graphene-reinforced hydrogel scaffold at 0.2% w/v creates a synergistic electromechanical microenvironment, robustly promoting hMSC osteogenesis, and offers a scalable platform for next-generation bone tissue engineering.